2015
DOI: 10.1371/journal.pone.0124262
|View full text |Cite
|
Sign up to set email alerts
|

The Gender-Dependent Association between Obesity and Age-Related Cataracts in Middle-Aged Korean Adults

Abstract: The aim of this study was to investigate the association of central and abdominal obesity with the prevalence of cataracts in a middle-aged Korean population. This retrospective cross-sectional study was based on the data collected from the Korea National Health and Nutrition Examination Survey 2008–2009, in which 4,914 subjects were examined. Ophthalmological examinations were performed to determine the presence of a nuclear, cortical, or posterior subcapsular cataract. Both general obesity (a body mass index… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Studies have shown an association between gentamicin toxicity and vision loss [30] however its role in the development of cataracts is unknown. Overall there are mixed views about obesity in the literature [31][32][33]. Our study found all 6 of these risk factors to have 20% or high odds of leading to development of cataract.…”
Section: Discussionmentioning
confidence: 50%
“…Studies have shown an association between gentamicin toxicity and vision loss [30] however its role in the development of cataracts is unknown. Overall there are mixed views about obesity in the literature [31][32][33]. Our study found all 6 of these risk factors to have 20% or high odds of leading to development of cataract.…”
Section: Discussionmentioning
confidence: 50%
“…Obesity is generally believed to accelerate ARC [1,2,3]. Although few evidence support the protective role of obesity against the cataract formation process [25,26], several prospective observational studies have confirmed a positive longitudinal association between obesity and different subtypes of cataract [3].…”
Section: Discussionmentioning
confidence: 99%
“…Obesity may accelerate age-related cataractogenesis (ARC), although the exact mechanisms are poorly understood [1,2,3]. Increased oxidative stress caused by higher circulating leptin levels of obese subjects is involved in the development and/or progression of cataract.…”
Section: Introductionmentioning
confidence: 99%
“…This increasing trend is of concern as obesity is an important risk factor for many chronic conditions such as cardiovascular disease, 2 diabetes, 3 cancer, 4 osteoarthritis, 5 and depression. 6 Importantly, in addition to the commonly recognized health outcomes associated with obesity, there is an increasing body of literature suggesting that overweight and obesity are associated with poor ocular health (eg, cataract, [7][8][9][10] visual impairment, 11,12 and poor visual acuity 13 ). For example, an Australian study of 3654 participants aged ≥49 years identified obesity as a risk factor for both cortical (odds ratio…”
Section: Introductionmentioning
confidence: 99%